Phenol Removal from Aqueous Solution by Adsorption Technique Using Coconut Shell Activated Carbon - Zhi Hoong Ho; Liyana Amalina Adnan (Tecno Scientifica, 2024)
Trop. Aqua. Soil Pollut. 2021, 1 (2), 98-107